Healthy Lifestyle selama Pandemi Covid-19 pada Siswa Sekolah Menengah (SMP) - Miftakhus Salam; Diyah Yulistika Handayani (Malahayati Nursing Journal, 2023)
ABSTRACT The COVID-19 pandemic has changed the way of life. During the COVID-19 pandemic, learning activities are carried out online at home. Students study and just stay at home. This circumstance places restrictions on students, which interferes with the adoption of a healthy lifestyle. As the body's barrier against COVID-19 transmission during the pandemic, a healthy lifestyle is extremely important. To describe the healthy lifestyle of students during the COVID-19 pandemic. The research used descriptive quantitative with a proportionate stratified random sampling of 261 students. The research instrument used an HPLP-II questionnaire consisting of 38 questions on a Likert scale. 144 (55.2%) students have a moderate level of Health responsibility aspect, in the physical activity aspect, most students (152 students or 58.2%) were categorized in the moderate category. Moreover, in the nutritional eating pattern aspect, 132 students (51.3%) were in the moderate category, and the majority of students are in the good category of spiritual development, 136 students (52.1%). In the interpersonal relationship aspect, students (112 students or 42.9%) are mainly in the good category, and 133 students (51%) have stress management aspects in the moderate category. The results showed that the healthy lifestyle of SMP N 3 Pangkah students with an average score of 2,560,20.  More than half (55.6%) of SMP N 3 Pangkah students had a good healthy lifestyle during the COVID-19 pandemic.  Keywords: Covid-19, Healthy Lifestyle, Adolescents, Students  ABSTRAK Pandemi COVID-19 yang melanda dunia merubah tatanan kehidupan. Selama pandemi COVID-19, Aktivitas pembelajaran dilakukan di rumah secara online. Siswa belajar dan hanya berada di rumah saja. Keadaan ini memberikan keterbatasan pada siswa sehingga berpengaruh dalam penerapan healthy lifestyle. Healthy lifestyle sangat dibutuhkan pada pandemi COVID-19 sebagai pertahanan tubuh untuk mencegah penularan COVID-19. Untuk mengetahui gambaran healthy lifestyle siswa selama pandemi COVID-19. Metode penelitian yang digunakan adalah deskriptif kuantitatif dengan proportionate stratified random sampling kepada 261 siswa. Intsrumen berupa kuesioner HPLP-II yang terdiri dari 38 pertanyaan dalam skala Likert. Aspek tanggung jawab Kesehatan pada tingkatan sedang 144 (55,2%) siswa, aspek aktivitas fisik menunjukan mayoritas pada kategori sedang 152 (58,2%), aspek pola makan bernutrisi mayoritas siswa pada kategori sedang 132 (51,3%) siswa, aspek perkembangan spiritual siswa mayoritas pada kategori baik 136 (52,1%) siswa, aspek hubungan interpersonal siswa Sebagian besar pada kategori baik 112 (42,9%) siswa dan aspek manajemen stress mayoritas pada kategori sedang 133 (51%) siswa. Hasil penelitian menunjukan bahwa healthy lifestyle siswa SMP N 3 Pangkah dengan rata-rata skor 2,56±0,20. Lebih dari setengah (55,6%) siswa SMP N 3 Pangkah mempunyai healthy lifestyle selama pandemi COVID-19 yang baik.  Kata Kunci: Covid-19, Healthy Lifestyle, Remaja, Siswa